Progressive collapse assessment of medium‐rise reinforced concrete flat slab structures. (3rd March 2017) - Attia, Fatma; Salem, Hamed; Yehia, Nabil
Abstract : The progressive collapse resistance of a medium‐rise multistory reinforced concrete flat slab structure is evaluated numerically using the applied element method. The case study is designed according to ACI 318 and its progressive collapse is assessed in accordance with the Unified Facilities Criteria (UFC) guidelines. The numerical results show that the case study considered generally satisfies the limits of the UFC guidelines except for the case of near‐corner interior column loss at the 10th floor and edge shear wall loss at ground, 5th, 8th, and 10th floors. The removal of the edge shear walls on the higher floors caused a partial collapse.